Morphological Characters of Papaya ( Carica papaya L.) for Drought Tolerance - Noel+, Michael R.; Aguilar, Edna A.; San Pascual, Alangelico O. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 33 No 2 (2021), 2022)
Papaya plants ( Carica papaya L.) were assessed for tree and fruit morphological traits. During eight months of drought conditions, papaya plants showed signs of drought from March to May 2016. Drought affected fruit development and fruit qualities. Significant decrease in fruit weight, length, width, flesh thickness, and seed weight were observed in drought-affected papayas; however, total soluble solids (TSS) of fruit flesh were significantly higher compared to the TSS of fruits harvested during normal conditions. Drought-tolerant papaya trees were selected based on morphological responses. Drought-tolerant papaya trees were significantly taller and had thicker stems, wider crowns, and more functional green leaves compared to drought-affected trees. Selected plants that thrived well under drought condition were identified for use in breeding. Recovery of plants was evident in increase in fruit weight, length, and width. Correlation of fruit characters of selected drought-tolerant papaya trees revealed that fruit weight was strongly positively correlated with fruit length, fruit width, peel weight, flesh thickness, and TSS.
Keywords: Carica papaya, drought, fruit characters, recovery, tree characters